Low-dose penicillin in early life induces long-term changes in murine gut microbiota, brain cytokines and behavior - Sophie Leclercq (Nature Portfolio, 2017)
There is concern about potential long-term effects of antibiotics on children’s health. Here Leclercqet al. show, in mice, that low doses of penicillin during late pregnancy and early life induce lasting effects on the offspring, including alterations in gut microbiota, brain cytokine levels and behaviour.